HUBUNGAN MOTIVASI DAN DISIPLIN GURU SERTIFIKASI TERHADAP PROSES BELAJAR MENGAJAR PADA SMA NEGERI 1 ACEH BARAT DAYA - Irwansyah .; Murniati AR; Yusrizal . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2019)
The correlation betweeen motivation and discipline of certified teachers may influence the effectiveness of a teaching and learning process. The objective of this research were: (1) finding out the motivation of certified teachers, (2) identifying the discipline of certified teachers, and (3) correlating those teachers’ motivation and their discipline to the teaching and learning process at State Senior High School (SMAN) 1 of Southwest Aceh Regency. A quantitative approach was used in this research. All of the certified teachers (32 teachers) were the population members in this research and a number of 187 students were chosen as the research samples. The validity of the research instrument was tested with a formula of the Pearson Product Moment Correlation Coefficient (Pearson-r) while the reliability was tested with Alfa Cronbach Formula. The data were analyzed by using a computer program called SPSS. The results showed that (1) the teachers’ motivation was positively and significantly correlated to the teaching and learning process (r=0.521) with being responsible, having encouragement to be successful, developing skills, and loving challenges as the indicators. Additionally, it was found that (2) there was also a positive and significant correlation between the teachers’ discipline and the teaching and learning process (r=0.726) with complying with the terms, obeying the rules, wanting to do the tasks, and being responsible as the indicators. In addition, (3) the motivation and the discipline of the certified teachers simultaneously, positively, and significantly influenced the teaching and learning process (72.8%) with making a plan, being professional, evaluating, conducting classroom action reesearch, and cooperating as the indicators. Hence, only 27.2 percent of the teaching and learning process was influenced by other factors.Keywords: Motivation, Discipline, Certified Teacher, Teaching and Learning Process